The role of electromagnetic interactions in second harmonic generation from plasmonic metamaterials - Alberti, Julian; Linnenbank, Heiko; Linden, Stefan; Grynko, Yevgen; Förstner, Jens (Applied Physics B)
We report on second harmonic generation spectroscopy on a series of rectangular arrays of split-ring resonators. Within the sample series, the lattice constants are varied, but the area of the unit cell is kept ﬁxed. The SHG signal intensity of the different arrays upon resonant excitation of the fundamental plasmonic mode strongly depends on the respective arrangement of the split-ring resonators. This ﬁnding can be explained by variations of the electromagnetic interactions between the split-ring resonators in the different arrays. The experimental results are in agreement with numerical calculations based on the discontinuous Galerkin time-domain method. (PDF) The role of electromagnetic interactions.... Available from: https://www.researchgate.net/publication/297612326_The_role_of_electromagnetic_interactions_in_second_harmonic_generation_from_plasmonic_metamaterials [accessed Aug 13 2018].
Keywords: tet_topic_shg; tet_topic_meta

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai-Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

Coherent photocurrent spectroscopy of single InP-based quantum dots in the telecom band at 1.5 µm - Gordon, S.; Yacob, M.; Reithmaier, J. P.; Benyoucef, M.; Zrenner, Artur (Applied Physics B)
In this work we study the resonant and coherent properties of single InP-based InAs quantum dots, which show an optical emission in the telecom C-band and L-band. High-resolution resonant photocurrent spectroscopy on p–i–n devices reveals narrow linewidths and fully resolved fine structure splittings. We observe Lorentzian line shapes, which allow for the extraction of dephasing times as a function of the applied bias voltage. Coherent ps laser excitation results in pronounced Rabi rotations with increasing pulse area. For π-pulse excitation, we obtain more than 93 % of the theoretically expected photocurrent amplitude. Our results also demonstrate that such state-of-the-art InP-based quantum dots for the telecom band exhibit promising key parameters comparable to well-established InAs/GaAs counterparts.
Keywords: Bias Voltage; Optical Parametric Oscillator; Molecular Beam Epitaxy Growth; Internal Electric Field; Dephasing Time

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Towards a quantum interface between telecommunication and UV wavelengths: design and classical performance - Rütz, Helge; Luo, Kai-Hong; Suche, Hubertus; Silberhorn, Christine (Applied Physics B)

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

Quantum interference control of electrical currents in GaAs microstructures: physics and spectroscopic applications - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Thunich, S.; Duc, H. T.; Podzimski, R.; Meier, Torsten; Betz, M. (Applied Physics B)

Advanced optical manipulation of carrier spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Meier, Torsten; Zrenner, Artur; Bayer, M. (Applied Physics B)
Spins in semiconductor quantum dots have been considered as prospective quantum bit excitations. Their coupling to the crystal environment manifests itself in a limitation of the spin coherence times to the microsecond range, both for electron and hole spins. This rather short-lived coherence compared to atomic states asks for manipulations on timescales as short as possible. Due to the huge dipole moment for transitions between the valence and conduction band, pulsed laser systems offer the possibility to perform manipulations within picoseconds or even faster. Here, we report on results that show the potential of optical spin manipulations with currently available pulsed laser systems. Using picosecond laser pulses, we demonstrate optically induced spin rotations of electron and hole spins. We further realize the optical decoupling of the hole spins from the nuclear surrounding at the nanosecond timescales and demonstrate an all-optical spin tomography for interacting electron spin sub-ensembles.
Keywords: Spin Polarization; Pump Pulse; Trion; Spin Component; Coherence Time

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Liquid-nitrogen cooled, free-running single-photon sensitive detector at telecommunication wavelengths - Covi, M.; Pressl, B.; Günthner, T.; Laiho, K.; Krapick, Stefan; Silberhorn, Christine; Weihs, G. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, B.; Elser, D.; Bartley, Tim; Sabuncu, M.; Wittmann, C.; Sych, D.; Marquardt, C.; Leuchs, G. (Applied Physics B)

Electromagnetic induction in metamaterials - Meyrath, T. P.; Zentgraf, Thomas; Rockstuhl, C.; Giessen, H. (Applied Physics B)

Influence of particle size and concentration on the second-harmonic signal generated at colloidal surfaces - Schneider, L.; Schmid, Hans-Joachim; Peukert, W. (Applied Physics B)
Second harmonic generation (SHG) spectroscopy is a recently developed technique for the investigation of surface properties of particles. To apply the method to technical colloidal systems, the dependences of several experimental parameters on the signal have to be studied. In this work the influence of particle concentration on the SHG signal from the surfaces of colloids (polystyrene beads in a size range of 0.1 μm to 2.9 μm) is investigated. A simple model, based on Lambert–Beer’s law, to describe the measured dependences is derived. The model agrees with the experimental observations for particles smaller 1.1 μm and with a small modification also for larger particles. Based on the new model an analytical equation for determining the optimum concentration, where highest signals in colloidal SHG spectroscopy measurements are obtained, is derived.

Optical switching in metallic photonic crystal slabs with photoaddressable polymers - Nau, D.; Bertram, R.P.; Buse, K.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S.G.; Gippius, N.A.; Giessen, H. (Applied Physics B)

Resonances of split-ring resonator metamaterials in the near infrared - Rockstuhl, C.; Zentgraf, Thomas; Guo, H.; Liu, N.; Etrich, C.; Loa, I.; Syassen, K.; Kuhl, J.; Lederer, F.; Giessen, H. (Applied Physics B)

Origin of reciprocal circular birefringence observed in X-cut, Z-propagation LiNbO3 polarization transformers - Bhandare, S; Noé, Reinhold; Sandel, D (APPLIED PHYSICS B-LASERS AND OPTICS)

Optimization of TE-TM mode converters on X-cut, Y-propagation LiNbO3 used for PMD compensation - Bhandare, S; Noé, Reinhold (APPLIED PHYSICS B-LASERS AND OPTICS)

Optical storage effect in a platinum orthometalated liquid crystal - Buey, J.; Díez, L.; Espinet, P.; Kitzerow, Heinz-Siegfried; Miguel, J.A. (Applied Physics B: Lasers and Optics)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Storage of laser-induced holographic gratings in discotic liquid crystals - Contzen, J.; Heppke, G.; Kitzerow, Heinz-Siegfried; Krüerke, D.; Schmid, H. (Applied Physics B Laser and Optics)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering